2014
DOI: 10.1186/s13550-014-0070-2
|View full text |Cite
|
Sign up to set email alerts
|

FBPA PET in boron neutron capture therapy for cancer: prediction of 10B concentration in the tumor and normal tissue in a rat xenograft model

Abstract: BackgroundBoron neutron capture therapy (BNCT) is a molecular radiation treatment based on the 10B (n, α) 7Li nuclear reaction in cancer cells, in which delivery of 10B by 4-borono-phenylalanine conjugated with fructose (BPA-fr) to the cancer cells is of critical importance. The PET tracer 4-borono-2-18 F-fluoro-phenylalanine (FBPA) has been used to predict the accumulation of BPA-fr before BNCT. However, because of the difference in chemical structure between BPA-fr and FBPA and the difference in the dose adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 24 publications
0
51
0
1
Order By: Relevance
“…First, organs that include air such as the intestine and lung could be evaluated without underestimation by the same protocol in both the L-BPA group and [ 19 F]-L-FBPA group in this study. In particular, [ 18 F]-L-FBPA accumulation in hollow organs or the lung is significantly underestimated by PET based on the maximum or average counts [16]. In this study, the boron concentrations of the intestine and lung showed no significant difference between the L-BPA group and [ 19 F]-L-FBPA group.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…First, organs that include air such as the intestine and lung could be evaluated without underestimation by the same protocol in both the L-BPA group and [ 19 F]-L-FBPA group in this study. In particular, [ 18 F]-L-FBPA accumulation in hollow organs or the lung is significantly underestimated by PET based on the maximum or average counts [16]. In this study, the boron concentrations of the intestine and lung showed no significant difference between the L-BPA group and [ 19 F]-L-FBPA group.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have compared the radioactivity accumulation of [ 18 F]-L-FBPA in tumour and normal tissues by PET as well as the boron concentrations of L-BPA in tumour and normal tissues by ICP-AES [16, 20, 21]. Ishiwata and colleagues examined the effect of L-BPA loading on the uptake of [ 18 F]-L-FBPA by measuring the radioactivity of 18 F in B16 melanoma-bearing mice [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our animal studies demonstrated that 18 F‐FBPA uptake was significantly associated with boron concentration in 6 tumors, despite the fact that the administered dose of 18 F‐FBPA is different from that of BPA. Hanaoka et al recently revealed an association between BPA and 18 F‐FBPA uptakes by bolus injection in RGC‐6 rat glioma and normal tissues. Wang et al also demonstrated that tumor uptake of BPA or 18 F‐FBPA reached maximum levels at 1 hour following bolus injection, which indicated their similar pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…BPA has the structure of phenylalanine that can be recognized mainly by LAT1 amino acid transporters overexpressed on many cancer cells, thereby permitting efficient cellular internalization (5,6). In addition, fluorinated BPA ( 18 F-BPA) was recently developed for companion diagnostics, and it has been experimentally demonstrated that 18 F-BPA exhibits similar biodistribution to the unfluorinated BPA (7,8) and allows us to quantitatively illustrate tumor accumulation of BPA and select patients who are likely to receive benefit from BNCT (9).…”
Section: Introductionmentioning
confidence: 99%